Genetic Variants in RKIP Are Associated with Clear Cell Renal Cell Carcinoma Risk in a Chinese Population - Cao, Qiang; Wang, Jian; Zhang, Mingcong; Li, Pu; Qian, Jian; Zhang, Shaobo; Zhang, Lei; Ju, Xiaobing; Wang, Meilin; Zhang, Zhengdong; Li, Jie; Gu, Min; et al. (PloS one, 2014)
Raf-1 kinase inhibitor protein (RKIP) plays a critical role in tumor development by regulating cell functions such as invasion, apoptosis and differentiation. Down-regulation of RKIP expression has been implicated in the development and progression of renal cell carcinoma (RCC). Herein, we hypothesized that genetic polymorphisms in RKIP might be associated with susceptibility and progression of RCC. A total of 5 tagging single-nucleotide polymorphisms (tSNPs) in RKIP were selected and genotyped by SNapShot method in a case-control study of 859 RCC patients and 1004 controls. The logistic regression was used to evaluate the genetic association with occurrence and progression of RCC. The functionality of the important SNP was preliminary examined by qRT-PCR. We found that the rs17512051 in the promoter region of RKIP was significantly associated with decreased clear cell RCC (ccRCC) risk (TA/AA vs. TT: P = 0.039, OR = 0.78, 95%CI = 0.62-0.99). Another SNP (rs1051470) in the 3'UTR region of RKIP was marginally associated with increased ccRCC risk (TT vs. CC+CT: OR = 1.45, 95%CI = 1.01-2.09). In the stratified analysis, the protective effect of rs17512051 was more predominant in the subgroups of male, non-smokers, non-drinkers as well as subjects without history of diabetes. Furthermore, we observed higher RKIP mRNA levels in the presence of the rs17512051A allele in normal renal tissues. Our results suggest that the potentially functional RKIP rs17512051 polymorphism may affect ccRCC susceptibility through altering the endogenous RKIP expression level. Risk effects and the functional impact of this polymorphism need further validation.